2017
DOI: 10.1063/1.4997926
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogen on the device performance and stability characteristics of amorphous InGaZnO thin-film transistors with a SiO2/SiNx/SiO2 buffer

Abstract: We investigate the influence of the multi-layered buffer consisting of SiO2/SiNx/SiO2 on amorphous InGaZnO (a-IGZO) thin-film transistors (TFTs). The multi-layered buffer inhibits permeation of water from flexible plastic substrates and prevents degradation of overlying organic layers. The a-IGZO TFTs with a multi-layered buffer suffer less positive bias temperature stress instability compared to the device with a single SiO2 buffer layer after annealing at 250 °C. Hydrogen from the SiNx layer diffuses into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 24 publications
2
36
0
Order By: Relevance
“…The minimum channel length of operational TFTs is here determined by the in-diffusion of hydrogen into the channel area. It has been reported 11,12 that there exists a critical hydrogen density in the semiconductor, below which hydrogen can suppress electron trapping associated with interstitial oxygen defects, leading to increased performance and stability; excessive hydrogen, on the other hand, causes formation of band edge states, resulting in a conductive channel, as observed here. It is thus important to control the hydrogen content, which is typically dependent on 1. the specifics of the doping process during the deposition of the silicon nitride intermetal dielectric; 2. the background hydrogen content and the hydrogen diffusion characteristics of the buffer, semiconductor, and gate insulator layers; and 3. the detailed annealing steps that the TFT stack undergoes during manufacturing.…”
Section: Sald Buffer Layersupporting
confidence: 63%
“…The minimum channel length of operational TFTs is here determined by the in-diffusion of hydrogen into the channel area. It has been reported 11,12 that there exists a critical hydrogen density in the semiconductor, below which hydrogen can suppress electron trapping associated with interstitial oxygen defects, leading to increased performance and stability; excessive hydrogen, on the other hand, causes formation of band edge states, resulting in a conductive channel, as observed here. It is thus important to control the hydrogen content, which is typically dependent on 1. the specifics of the doping process during the deposition of the silicon nitride intermetal dielectric; 2. the background hydrogen content and the hydrogen diffusion characteristics of the buffer, semiconductor, and gate insulator layers; and 3. the detailed annealing steps that the TFT stack undergoes during manufacturing.…”
Section: Sald Buffer Layersupporting
confidence: 63%
“…Particularly, hydrogen has a strong inuence on the D1 state, whereas the D2 state is dependent on the process parameters of the oxide semiconductors. 16,17 Since we performed the SE analysis on the same sample, the only difference is the existence/nonexistence of X-ray irradiation. For this reason, it is obvious that the increase in relative area of the D1 and D2 states is caused by X-ray irradiation and strongly associated with the electron generation in a-IGZO lm, which will be discussed later in more detail.…”
Section: Resultsmentioning
confidence: 99%
“…When the SiNx-SiOx-SiNx sandwich structure was used as buffer layer, the transmittance shown regularity with different film-forming temperature and film thickness. As can be seen from Fig 2(b), the transmittance of SiNx-SiOx-SiNx (1K-4K-1K Å, deposited on cPI at 285/295℃) layer decreases near the wavelength of 510nm and 670nm, and the transmittance of SiNx-SiOx-SiNx (0.5K-1K-0.5K Å, deposited on cPI at 360/380℃) structure decreases at 600nm, these results are yellowing phenomenon in macroscopic view [7] . Particularly, when SiO2 is directly deposited on cPI, the transmittance of 380 nm to 620 nm also decreases ( Fig.…”
Section: The Influence Of Film-forming Temperature and Film Structurementioning
confidence: 79%
“…This is illustrated as a schematic diagram in Fig 5(c). Hydrogen related defects may also have generated hole carriers within the semiconductor layer, and upon NBTIS, hole trapping near the IGZO-gate dielectric could have occurred [6,7] . It is also suggested that the relatively large shallow density of localized gap states (DOS) distribution would be related to the presence of donor-like states originating from water molecules, which were diffused through the buffer layer from the cPI substrates and H2O reservoir, thus resulting in negative Vth shifts and hump phenomenon [10] .…”
Section: Wvtr Testmentioning
confidence: 99%